Wick system – An efficacious techniquefor gerbera cultivation - S, Sangeetha Priya; C, Aswath; S A, Safeena (Indian Horticulture, 2024)
Gerbera, being the most globally-traded flower crop, is commercially grown on soil beds using drip irrigation system. Although drip system saves 30-50% of water compared to the traditional irrigation methods, there is an increasing urge to improve the water- and nutrient-use efficiency of the crop by adopting efficient production system in the present context of expanding urbanization, diminishing agricultural area and reducing water availability. Wick system which exploits the principle of capillary action is one such technique that could effectively enhance the production and quality along with increased net returns and water saving. Adopting wick system for gerbera increased the flower production by 53% and water saving by 44% over the drip system. Moreover, the physical and chemical properties of the soil are least bothered under wick system as there is no external force or pressure exerted on the soil unlike the trickling water droplets in drip system. Hence, the superior crop performance of gerbera could be considered as the resultant of lesser soil compaction, consistent water availability and better soil physical properties under wick system.